(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the cognitive dimensions of French phraseological units (PUs) within the framework of communicative space. Drawing on the theories of conceptual metaphor (Lakoff & Johnson, 1980), conceptual integration (Fauconnier & Turner, 2002), and image schemas (Johnson, 1987), the paper demonstrates how idiomatic expressions in French encapsulate culturally embedded knowledge, metaphorical reasoning, and pragmatic intent. French idioms such as avoir le cafard, mettre les pieds dans le plat, and tomber des nues exemplify how figurative language emerges from mental space interaction and embodied experience. The study further examines the discourse functions of PUs—such as irony, solidarity, and intensification—and explores mechanisms of phraseological innovation, including neologization, ellipsis, and recontextualization. Additionally, intercultural aspects are analyzed, showing how idioms reflect national identity and cognitive-cultural variation. The findings highlight the role of phraseological units as dynamic cognitive tools for discourse construction, social interaction, and conceptualization, thereby contributing to a deeper understanding of the link between language, thought, and culture in contemporary French.